Sertifikasi JULEHA sebagai Upaya Peningkatan Ekonomi Masyarakat Kabupaten Lombok Barat Provinsi Nusa Tenggara Barat - Herawati; Aulanni’am; Junining, Esti; Suprapto (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
To support the implementation of the President’s instructions to boost investment in various regions in Indonesia, the West Lombok Regency Government, in the West Nusa Tenggara Province (NTB), through the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN). Is striving to create an investmentfriendly climate through the Spatial Detail Plan (RDTR). Various elements that support the readiness of the RDTR program need to be prepared thoroughly, including the provision of standardized halal meat products, the application of science and technology, and mapping the potential at the Slaughterhouse (RPH) needs improvement. Additionally, important factors to consider include halal aspects and animal welfare to meet market needs where the resulting slaughtered livestockes meets the ASUH criteria (Safe, Healthy, Intact, and Halal). Unfortunately, only 10 butchers in the entire NTB have Veterinary Control Numbers (NKV) and are certified Halal Slaughterers (Juleha) by the National Certification Profession Agency (BNSP). The readiness of certified Juleha butchers needs to be improved to achieve the continuity of ASUH processed meat products. From this community service activity, there are a total of 20 butchers who have passed the test and obtained Juleha certification. The butcher program for butchers who have Juleha certification is a subsequent step that has been agreed upon by the community service team and the NTB Government.